Impaired Neurite Contact Guidance in Ubiquitin Ligase E3a (Ube3a)‐Deficient Hippocampal Neurons on Nanostructured Substrates. Issue 7 (4th February 2016) - Tonazzini, I.; Meucci, S.; Van Woerden, G. M.; Elgersma, Y.; Cecchini, M.
Abstract : Recent discoveries indicate that during neuronal development the signaling processes that regulate extracellular sensing (e.g., adhesion, cytoskeletal dynamics) are important targets for ubiquitination‐dependent regulation, in particular through E3 ubiquitin ligases. Among these, Ubiquitin E3a ligase (UBE3A) has a key role in brain functioning, but its function and how its deficiency results in the neurodevelopmental disorder Angelman syndrome is still unclear. Here, the role of UBE3A is investigated in neurite contact guidance during neuronal development, in vitro. The microtopography sensing of wild‐type and Ube3a‐deficient hippocampal neurons is studied by exploiting gratings with different topographical characteristics, with the aim to compare their capabilities to read and follow physical directional stimuli. It is shown that neuronal contact guidance is defective in Ube3a‐deficient neurons, and this behavior is linked to an impaired activation of the focal adhesion signaling pathway. Taken together, the results suggest that the neuronal contact sensing machinery might be affected in Angelman syndrome. Abstract : The performance of neurite contact guidance and adhesion signaling is addressed in Ubiquitin ligase E3a (Ube3a)‐deficient hippocampal neurons (Angelman syndrome model). By using nanogrooved substrates, impairments in the contact guidance and neurite polarization of Ube3aKO neurons in response to pure topographical signals are demonstrated and this behavior is linked to the impaired activation of focal adhesion pathway.